1977
DOI: 10.2466/pr0.1977.40.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocity in Self-Disclosure within the Psychological Interview

Abstract: 24 male and 24 female college subjects were interviewed individually by a male graduate student, using standardized interviews. Intimacy of subjects' self-disclosures during the interviews was investigated in relation to interviewing style (reflecting versus disclosing), seating arrangement (presence or absence of intervening desk), sex of subjects, and the temporal sequence of the interview. Results showed a significant correlation of intimacy of self-disclosure as measured by judges' content ratings of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…17; Kaiser, 1965) who have argued that self-disclosure by the therapist can enhance the relationship between therapist and client. Moreover, it underscores previous findings that when therapists self-disclose, clients are more likely to see the therapist as friendly, open, helpful, and warm (Dies, 1973; Feigenbaum, 1977; May & Thompson, 1973; Murphy & Strong, 1972).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…17; Kaiser, 1965) who have argued that self-disclosure by the therapist can enhance the relationship between therapist and client. Moreover, it underscores previous findings that when therapists self-disclose, clients are more likely to see the therapist as friendly, open, helpful, and warm (Dies, 1973; Feigenbaum, 1977; May & Thompson, 1973; Murphy & Strong, 1972).…”
Section: Discussionsupporting
confidence: 71%
“…Instead, most past research has focused on the relation between therapist self-disclosure and the process of therapy. For example, studies have examined the relation between therapist self-disclosure and the frequency of client self-disclosure (Bundza & Simonson, 1973; Halpern, 1977; Mann & Murphy, 1975; Simonson, 1976; Simonson & Bahr, 1974; Wetzel & Wright-Buckley, 1988), the intimacy of client self-disclosure (Feigenbaum, 1977), and client perceptions of the therapist (Dies, 1973; Doster & Brooks, 1974; Feigenbaum, 1977; Fox, Strum, & Walters, 1984; Halpern, 1977; Hill, Mahalik, & Thompson, 1989; Hoffman & Spencer, 1977; Mann & Murphy, 1975; May & Thompson, 1973; Murphy & Strong, 1972). Although one study examined the possible correlation between therapist disclosure and treatment outcome (Hill et al, 1988), past researchers have never systematically varied levels of therapist self-disclosure to assess whether these disclosures can have a causal influence on therapy outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In these analogue studies, participants (usually undergraduate psychology students participating for course credit) have been presented with a disclosure stimulus embedded in a written transcript, audiotape, or videotape of a hypothetical therapy session, after which they rate their perceptions of the disclosure or of the therapist. Of 18 analogue studies of therapist self-disclosure in individual therapy, 14 reported positive perceptions of therapist self-disclosure (Bundza & Simonson, 1973; Doster & Brooks, 1974; Dowd & Boroto, 1982; Feigenbaum, 1977; Fox, Strum, & Walters, 1984; Hoffman-Graff, 1977; Myrick, 1969; Nilsson, Strassberg, & Bannon, 1979; Peca-Baker & Friedlander, 1987; Simonson, 1976; Simonson & Bahr, 1974; VandeCreek & Angstadt, 1985; Watkins & Schneider, 1989; Wetzel & Wright-Buckley, 1988), 3 reported negative perceptions (Carter & Motta, 1988; Cherbosque, 1987; Curtis, 1982), and 1 reported mixed findings (Goodyear & Shumate, 1996). In his review of this analogue literature, Watkins (1990) concluded that therapists who self-disclosed in a moderate or nonintimate way have been viewed more favorably and have elicited more client self-disclosure than therapists who did not disclose at all, who disclosed a lot, or who disclosed very intimate material.…”
Section: Perceptions Of Therapist Self-disclosure By Nonclientsmentioning
confidence: 99%
“…Other studies (e.g., Dies, 1973;Feigenbaum, 1977;Jourard & Friedman, 1970;Murphy & Strong, 1972;Vondracek& Vondracek, 1971) have shown that the use of therapist selfdisclosure favorably influences clients' perceptions necessary to the development of a strong therapeutic alliance; these findings, of course, are consistent with a humanisticexistential and/or behavioristic perspective.…”
Section: Introductionmentioning
confidence: 79%